Prevalence of Myopia and its Risk Factors in Elementary School Children - Nabila Maharani Ahmadi Putri; Praminto Nugroho (Pusat riset dan Inovasi Nasional, 2026)
Myopia is a multifactorial disease, affected by various hereditary and environmental conditions. This literature review aims to evaluate the association between risk factors in incidence of myopia in children aged 6 to 12 years old. A cross-sectional study of elementary students in MI Patihan Kidul, Ponorogo, East Java was performed. Eligible samples were 6 to 12 years old students. Examination was performed on September 7th 2023. The students underwent short history taking, body mass index (BMI), and visual acuity examination. Age, sex, BMI, family history of myopia, sleeping time, screen time, and duration of outdoor activity were examined as risk factors. A total of 336 children met the inclusion criteria, of which 48 (14.2%) of them had myopia. Family history of myopia was proven to increase the risk for myopia on their children (p value 0.012, OR 0.436). Heredity is a well-established risk factor for myopia. This literature review provides evidence on the positive correlation between family history and the occurrence of myopia in children.